Quercetin Inhibits Inflammatory Response Induced by LPS from Porphyromonas gingivalis in Human Gingival Fibroblasts via Suppressing NF-κB Signaling Pathway. (20th August 2019) - Xiong, Gang; Ji, Wansheng; Wang, Fei; Zhang, Fengxiang; Xue, Peng; Cheng, Min; Sun, Yanshun; Wang, Xia; Zhang, Tianliang
Abstract : Quercetin, a natural flavonol existing in many food resources, has been reported to be an effective antimicrobial and anti-inflammatory agent for restricting the inflammation in periodontitis. In this study, we aimed to investigate the anti-inflammatory effects of quercetin on Porphyromonas gingivalis ( P. gingivalis ) lipopolysaccharide- (LPS-) stimulated human gingival fibroblasts (HGFs). HGFs were pretreated with quercetin prior to LPS stimulation. Cell viability was evaluated by 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. The levels of inflammatory cytokines, including interleukin-1 β (IL-1 β ), interleukin-6 (IL-6), and tumor necrosis factor- α (TNF- α ), along with chemokine interleukin-8 (IL-8), were determined by enzyme-linked immunosorbent assay (ELISA). The mRNA levels of IL-1 β, IL-6, IL-8, TNF- α, I κ B α, p65 subunit of nuclear factor-kappa B (NF- κ B), peroxisome proliferator-activated receptor- γ (PPAR- γ ), liver X receptor α (LXR α ), and Toll-like receptor 4 (TLR4) were measured by real-time quantitative PCR (RT-qPCR). The protein levels of I κ B α, p-I κ B α, p65, p-p65, PPAR- γ, LXR α, and TLR4 were characterized by Western blotting. Our results demonstrated that quercetin inhibited the LPS-induced production of IL-1 β, IL-6, IL-8, and TNF- α in a dose-dependent manner. It also suppressed LPS-induced NF- κ B activation mediated by TLR4. Moreover, the anti-inflammatory effects of quercetin were reversed by the PPAR- γ antagonist of GW9662. In conclusion, these results suggested that quercetin attenuated the production of IL-1 β, IL-6, IL-8, and TNF- α in P. gingivalis LPS-treated HGFs by activating PPAR- γ which subsequently suppressed the activation of NF- κ B.